Implementasi Sema Nomor 3 Tahun 2023 di Pengadilan Agama Samarinda (Studi Terhadap Persepsi Para Pihak) - Sirri Khairul Inayah; Darmawati; Lilik Andaryuni (Bulletin of Community Engagement, 2024)
Marriage agreements based on their benefits in fact do not run as they should because many people still do not understand how important marriage agreements are to protect women’s rights in marriage, so this research aims to analyze the marriage agreement influencing the Decision of the Panel of Judges in the division of joint property and examine the concept of separation of property in the household contained in the marriage agreement from a legal purpose perspective. The results of this study indicate that (a). the division of joint assets in the Religious Court sees the existence of a Marriage Agreement, namely the Samarinda Religious Court Number 1726 / Pdt.G / 2019 / PA.Smd and the Balikpapan Religious Court Number 1672 / Pdt.G / 2023 / PA.Bpp, prioritizes maslahah, namely an effort to bring benefits and goodness by rejecting harm that will cause damage to humans, this is known as the substantive justice of the judge as a case resolver who fulfills the sense of justice of the community, while for cases where there is no marriage agreement, the Panel of Judges adjudicates in accordance with Article 97 and Article 98 of the Compilation of Islamic Law in conjunction with Article 35 of Law No. 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage, namely dividing joint assets for the wife ½ part and the husband ½ part, b) Marriage Agreement in accordance with Jeremy Bentham's opinion where the law must contain legal objectives in the form of maximum benefits for many people, by fulfilling several factors, namely to provide a living, to provide abundant food, to provide protection, to achieve equality, then the Marriage Agreement can protect the wife's rights in marriage